Adhesive ligand tether length affects the size and length of focal adhesions and influences cell spreading and attachment - Attwood, Simon J. (Sci Rep, 2016)
Cells are known to respond to physical cues from their microenvironment such as matrix rigidity. Discrete adhesive ligands within flexible strands of fibronectin connect cell surface integrins to the broader extracellular matrix and are thought to mediate mechanosensing through the cytoskeleton-integrin-ECM linkage. We set out to determine if adhesive ligand tether length is another physical cue that cells can sense. Substrates were covalently modified with adhesive arginylglycylaspartic acid (RGD) ligands coupled with short (9.5 nm), medium (38.2 nm) and long (318 nm) length inert polyethylene glycol tethers. The size and length of focal adhesions of human foreskin fibroblasts gradually decreased from short to long tethers. Furthermore, we found cell adhesion varies in a linker length dependent manner with a remarkable 75% reduction in the density of cells on the surface and a 50% reduction in cell area between the shortest and longest linkers. We also report the interplay between RGD ligand concentration and tether length in determining cellular spread area. Our findings show that without varying substrate rigidity or ligand density, tether length alone can modulate cellular behaviour.